Development of a clinically relevant ovarian cancer model incorporating surgical cytoreduction to evaluate treatment of micro-metastatic disease - Morse, Christopher B.; Voillet, Valentin; Bates, Breanna M.; Chiu, Edison Y.; Garcia, Nicolas M.; Gottardo, Raphael; Greenberg, Philip D.; Anderson, Kristin G. (Gynecologic oncology, 2021)
Mouse models of ovarian cancer commonly transfer large numbers of tumor cells into the peritoneal cavity to establish experimental metastatic disease, which may not adequately model early metastatic spread from a primary tumor site. We hypothesized we could develop an ovarian cancer model that predictably represents micro-metastatic disease. Murine ID8VEGF ovarian cancer cells were transduced to express enhanced luciferase (eLuc) to enable intravital detection of microscopic disease burden and injected beneath the ovarian bursa of C57Bl/6 mice. At 6 or 10 weeks after orthotopic injection, when mice had detectable metastases, hysterectomy and bilateral salpingo-oophorectomy was performed to remove all macroscopic disease, and survival monitored. Immunohistochemistry and gene expression profiling were performed on primary and metastatic tumors. eLuc-transduced ID8VEGF cells were brighter than cells transduced with standard luciferase, enabling in vivo visualization of microscopic intra-abdominal metastases developing after orthotopic injection. Primary surgical cytoreduction removed the primary tumor mass but left minimal residual disease in all mice. Metastatic sites that developed following orthotopic injection were similar to metastatic human ovarian cancer sites. Gene expression and immune infiltration were similar between primary and metastatic mouse tumors. Surgical cytoreduction prolonged survival compared to no surgery, with earlier cytoreduction more beneficial than delayed, despite micro-metastatic disease in both settings. Mice with primary ovarian tumors established through orthotopic injection develop progressively fatal metastatic ovarian cancer, and benefit from surgical cytoreduction to remove bulky disease. This model enables the analysis of therapeutic regimens designed to target and potentially eradicate established minimal residual disease. •Orthotopic tumor inoculation establishes a progressive primary tumor that disseminates to form metastatic disease.•Metastases recapitulate the immune profile of the originating primary tumor and metastatic human disease.•Surgical cytoreduction of primary tumors prolongs survival.•Surgical cytoreduction retains micro-metastatic disease for evaluating therapeutic interventions.